A quantitative examination of punishment research. (January 2015) - Lydon, Sinéad; Healy, Olive; Moran, Laura; Foody, Ciara
Highlights: The publication of punishment procedures was highest in the early 1980s. A decline in the number of studies utilizing punishment has emerged over the decades. Since 1990 punishment procedures are reported in less than ten articles each year. Abstract: The current review examined 368 articles, published between 1967 and 2013, which evaluated punishment-based procedures for the treatment of challenging behavior among persons with developmental disabilities and quantitatively analyzed: (a) the amount of research that has assessed different types of punishment procedures; (b) the characteristics of the participants, behaviors, and treatments included in these studies, and (c) the relative efficacy of the various punishment procedures in general and with regard to the inclusion of reinforcement-based components, method of treatment selection and development, and function of the targeted challenging behaviors. Further, the study evaluated the included studies for the presence of important quality indicators. It was intended that such an analysis would provide a useful overview of the extant research on punishment procedures as a behavior reduction technique. Suggestions regarding research methodology and areas for further investigation are made for future research evaluating punishment-based interventions.